The Influence of Sharia Financial Literacy, Risk Tolerance, and Financial Attitudes on Sharia Investment Decisions - Erick Nathaniela Watiningtiyas; Amrul Hinung Prihamayu (Falahiya Journal of Islamic Banking and Finance, 2025)
Introduction: This study explores how Islamic financial literacy, risk tolerance, and financial attitude affect Islamic investment decisions. Despite growing interest in sharia-compliant finance, actual participation remains low. This gap highlights the importance of understanding the behavioural factors that influence Muslim investors. Research Methods: The research method employed a quantitative approach, involving a survey of 100 individual investors in Surabaya. Data were analysed using Partial Least Squares (PLS) with SmartPLS 3.2.9 to examine the relationship between the variables. Results: The analysis shows that Islamic financial literacy, risk tolerance, and financial attitude each have a positive and significant influence on Islamic investment decisions, supporting the behavioural finance perspective in a sharia context. Conclusion: The study concludes that Islamic financial literacy, risk tolerance, and financial attitude significantly influence Islamic investment decisions. These findings highlight the need to enhance financial education and awareness to boost participation in sharia-compliant investments.